Rosuvastatin's effects on ischemic skin flaps: Facts about statins' effects on skin flap viability (Annals of Medical Research, 2021)
Aim: Statins are considered to be protective against ischemic injury because of their pleiotropic effects. In this animal study, theeffects of high dose (40 mg/kg) rosuvastatin on ischemic skin flaps were investigated.Materials and Methods: Eighteen Wistar Albino male rats randomly divided into the treatment and the sham groups in equal numbers(n=9 in each group). Orogastric tubes were used both in the treatment and the sham group. Differently, in our study orogastric feedingstarted one day before the surgery and ended on the postoperative day seven. By this way we aimed to have enough circulatinglevels of agent in acute ischemia. Only the treatment group received rosuvastatin-supplemented water. Twenty-four hours after thefirst gavage application, caudally based, modified McFarlane flaps were elevated in 3x10 cm in size. After flap elevation procedure,the flaps were returned to their original location immediately.Results: The day after the last gavage application on postoperative day seven animals were sacrificed. Thereafter the digital imageswere obtained. The skin biopsies were taken by pathologist from three zones on each flap for histopathological assessment. Skinflap viability rate (p=0.508) and necrosis rate (p=0.453) did not show any difference between the groups Interestingly, the finalweights of the animals were lower than their initial weights, but this was only significant for the study group (p=0.008), not for thesham group (p=0.400). There were no any expectations related with weight change of the animals before the statistical analysis.Conclusion: On the other hand, there are literature studies claiming that the statins are effective to increase ischemic skin flapsviability, this study contradicts earlier studies. Statins were not observed to have favorable effects on critically ischemic skin flapviability through their pleiotropic activity.
Keywords: Ischemic skin; flap viability; pleiotropic effects; statins; weight loss